IMPLEMENTASI FRAMEWORK LARAVEL PADA SISTEM ADMINISTRASI KEPENDUDUKAN ONLINE STUDI KASUS DESA SASAKPANJANG - Muchlis Widyoprakoso (2021)
The COVID-19 pandemic at the beginning of 2020 in the world forced many activities to be postponed or even canceled because it could cause crowds and increase the spread of disease. In addition, the current development of information technology in the industrial era 4.0 indicates that all activities are heading to the digital world. These two situations make things that concern people's lives have to be digitized, as well as the services of the population administration system in Indonesia. Sasakpanjang villageis inhabited by tens of thousands of people, the number of people living there also increases the number of needs for mail services. The online population administration service system has finally become a solution in suppressing the spread of COVID-19 and improving population administration services for Sasakpanjang Village in the industrial era 4.0. In making and designing the system using the waterfall model system development method, because it allows to minimize errors that occur and make the final result of making the system acceptable for all parties. The use of the Laravel framework makes developing web-based applications easier with the support of many object-oriented libraries, the availability of artisan tools, and lightweight layout templates that save time and speed up the development process. This study aims to increase the effectiveness and efficiency of village population administration services, as well as to break the chain of spread of COVID-19 by implementing an online population administration application system. The result of this research is a website-based online population administration application system.